Playing against the rhythm: the intersection of gender and performative space in Iran - Rafei, Leila (AUC Knowledge Fountain, 2012)
Since the Iranian Revolution of 1979, women have been legally prohibited from singing or playing a musical instrument solo in public. The government has sought to control women’s performative space by using concepts of permissibility and ideological compatibility. In the past decade, however, Iran has seen the birth of an underground music culture, in which women sing and play illegally. Underground and diasporic female musicians have carved new spaces that subvert state regulations on cultural purity and nationalism, deterritorializing and deconstructing notions of national space and culture. Women musicians have thus demonstrated the failure of the state to successfully regulate performative space.